Nightfall - Asimov, Isaac, 1920-1992.; Silverberg, Robert (New York : Bantam Books, 1991)
Kalgash is a world on the edge of chaos, torn between religious fanaticism and scientific rationalism. Their civilization is threatened by Nightfall, the first sunset in over two thousand years.
Keywords: Science fiction, American; Science fiction